Supravalvular Congenital Mitral Stenosis - Moraes,Fernando (2002)
Congenital supravalvular mitral stenosis is a rare malformation characterized by the presence of a shelf-like fibrous membrane, with 1 or 2 small orifices, covering and obstructing the mitral valve. The membrane is positioned closely to the mitral valve (and sometimes it is attached to it); therefore, a preoperative diagnosis is inevitably difficult, even with the use of biplane echocardiography. Two patients with supravalvular mitral stenosis aged 3 years and 3 months are described. In 1 patient, a preoperative diagnosis was made, and both successfully underwent correction.